2012
DOI: 10.1038/cdd.2012.38
|View full text |Cite
|
Sign up to set email alerts
|

Bid protects the mouse hematopoietic system following hydroxyurea-induced replicative stress

Abstract: Hematopoietic stem cells (HSCs) possess long-term self-renewal capacity and multipotent differentiative capacity, to maintain the hematopoietic system. Long-term hematopoietic homeostasis requires effective control of genotoxic damage to maintain HSC function and prevent propagation of deleterious mutations. Here we investigate the role of the BH3-only Bcl-2 family member Bid in the response of murine hematopoietic cells to long-term replicative stress induced by hydroxyurea (HU). The PI3-like serine/threonine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Surprisingly, a substantial decrease in transcript levels of the proapoptotic gene BID (BH3-interacting domain death agonist) was observed in Gli1 knockdown A549 cells (data not shown). Although Bid is well known for proapoptosis signaling, many recent studies confirmed its role in early DDR (50,56). Consistent with these studies, a transient exposure of cancer cells to CPT induced the expression of Bid at both transcript and protein levels in A549 (Figs.…”
Section: Gli1 Regulates the Atr-mediated Replication Checkpoint By Cosupporting
confidence: 71%
“…Surprisingly, a substantial decrease in transcript levels of the proapoptotic gene BID (BH3-interacting domain death agonist) was observed in Gli1 knockdown A549 cells (data not shown). Although Bid is well known for proapoptosis signaling, many recent studies confirmed its role in early DDR (50,56). Consistent with these studies, a transient exposure of cancer cells to CPT induced the expression of Bid at both transcript and protein levels in A549 (Figs.…”
Section: Gli1 Regulates the Atr-mediated Replication Checkpoint By Cosupporting
confidence: 71%
“…17,18 In addition, we have demonstrated a role for Bid in the DDR to replicative stress mediated by Atr. 19,21,33 To probe Atmindependent roles for Bid in vivo, we have crossed Bid À / À mice to Atm À / À mice. Surprisingly, we found that loss of Bid increases the latency of leukemogenesis in Atm À / À mice.…”
Section: Discussionmentioning
confidence: 99%
“…Bid thus functions at the level of the DNA damage sensor complex, and integrates DNA replicative stress signals. [19][20][21] A recent report, using mice harboring Bid mutated in the Atm/Atr phosphorylation sites that has been knocked into the Bid locus, has demonstrated that Atmmediated Bid phosphorylation has a role in protecting HSCs from irradiation and oxidative stress, suggesting the possibility that Bid may have a more general role in sensing stress. 22 An elegant series of experiments has recently demonstrated in the mouse model of lymphomagenesis induced by g irradiation that tumorigenesis is driven by repeated cycles of hematopoietic progenitor cell death, inducing compensatory mobilization of HSC and progenitor cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in wild-type mice under conditions of repeated replicative stress, the LSK and MPC cell populations are expanded, and bone marrow function is maintained as demonstrated by the ability to compete with unchallenged bone marrow to adequately repopulate lethally irradiated recipient mice. 62 Bid −/− MPCs are more sensitive to replicative stress, resulting in depletion of MPCs following HU. HSCs respond to this loss of progenitor cells by mobilizing to enter the cell cycle.…”
Section: Bid Integrates Stress Signals In Hematopoiesismentioning
confidence: 99%